MADAGASCAR: A BIODIVERSITY HOTSPOT STILL REVEALING ITS BOTANICAL TREASURES. (5th November 2020) - Clubbe, Colin; Cable, Stuart; Ralimanana, Hélène
Summary: The status of Madagascar's plant diversity is briefly reviewed, together with a consideration of the key threats and approaches used in conserving this unique flora. The role of the Kew Madagascar Conservation Centre is reviewed in relation to species discovery and conservation.